Temperature‐dependence improvement for a MEMS gyroscope using triangular‐electrode based capacitive detection method. (1st November 2017) - Lin, Yiyu; Zheng, Xudong; Liu, Siqi; Ma, Wei; Jin, Zhonghe
Abstract : This work presents analysis and test results on temperature‐dependence improvement for a microelectromechanical systems (MEMS) gyroscope based on triangular‐electrode based (TEB) capacitive detection method. To reduce the effects of temperature variations on MEMS gyroscopes, TEB capacitive detection method is applied because the extracted amplitude and phase are robust to system parameter fluctuations. In the first place, analytical results for the scale factors and zero‐rate outputs, respectively, utilising linear electromechanical amplitude modulation (linear‐EAM) method and TEB method are derived. Then experimental results of the temperature characteristics for gyroscopes are conducted. The temperature coefficient of scale factor over the temperature range of −10 to 60°C is reduced from −8845 ppm/°C for linear‐EAM method to 1660 ppm/°C for TEB method with an improvement factor of 5.3. Moreover, the temperature‐induced zero‐rate output variation is decreased from −68.05°/s for linear‐EAM method to −29.09°/s for TEB method with an improvement factor of 2.3. Experimental results of temperature‐dependence improvement agree well with the theoretical analysis. In the end, Allan variance analysis demonstrates a bias instability of 2.85°/h, and an ARW (angle random walk) of 0.16°/√h with a vacuum‐packaged gyroscope using TEB method, which is significantly better than the bias instability 5.47°/h and ARW 0.22°/√h tested using linear‐EAM method.